Effect of Specimen Shape and Size on the Compressive Strength of Foamed Concrete - Sudin, M.A.S.; Ramli, M. (EDP Sciences, 2014)
Lightweight concrete, in the form of foamed concrete, is a versatile material that primarily consists of a cement based mortar, mixed with at least 20% volume of air. Its dry density is typically below 1600 kg/m3 with a maximum compressive strength of 15MPa. The ASTM standard provision specifies a correction factor for concrete strength of between 14 and 42Mpa, in order to compensate for a reduced strength, when the aspect height-to-diameter ratio of a specimen is less than 2.0. However, the CEB-FIP provision specifically mentions a ratio of 150mm dia. x 300mm cylinder strength to 150 mm cube strength; though, both provision requirements do not specifically clarify the applicability and/or modification of the correction factors for the compressive strength to lightweight concrete (in this case, foamed concrete). The focus of this work is to study the effect of specimen size and shape on the axial compressive strength of concrete. Specimens of various sizes and shapes were cast with square and circular cross-sections i.e., cubes, prisms, and cylinders. Their compression strength behaviours at 7 and 28 days were investigated. The results indicate that, as the CEB-FIP provision specified, even for foamed concrete, 100mm cubes (l/d = 1.0) produce a comparable compressive strength with 100mm dia. x 200mm cylinders (l/d = 2.0).